TEMUAN NASKAH-NASKAH KUNO DI MASJID LAYUR, SEMARANG, JAWA TENGAH - Masyhudi Masyhudi (Berkala Arkeologi, 2012)
The findings of ancient manuscripts in the ancient mosque on Layur Street, District of North Semarang known as Kampung Arab and lettered entirely in Arabic. Manuscripts were found on the roof of the mosque in a very poor condition, as most texts estimated to number in the tens of manuscripts have been destroyed, it cannot be identified. Through this paper the author will present a descriptive picture of the manuscript codex found in the Mosque Layur Semarang Central Java.